2023
DOI: 10.1155/2023/4452414
|View full text |Cite
|
Sign up to set email alerts
|

Berberine in Sepsis: Effects, Mechanisms, and Therapeutic Strategies

Abstract: Sepsis is defined as a dysregulated immune response to infection that leads to multiple organ dysfunction. To date, though a growing body of knowledge has gained insight into the clinical risk factors, pathobiology, treatment response, and recovery methods, sepsis remains a significant concern and clinical burden. Therefore, further study is urgently needed to alleviate the acute and chronic outcomes. Berberine (BBR), a traditional Chinese medicine with multiple actions and mechanisms, has been investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Sepsis has been recognized as a life-threatening illness, characterized by multiorgan dysfunction, which results in high morbidity and mortality, with limited pharmacologic therapy ( 13 ). An immunosuppressive status is the main cause of increased mortality in patients with advanced sepsis ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis has been recognized as a life-threatening illness, characterized by multiorgan dysfunction, which results in high morbidity and mortality, with limited pharmacologic therapy ( 13 ). An immunosuppressive status is the main cause of increased mortality in patients with advanced sepsis ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated ER stress is related to inflammation ( 12 ). It is widely established that sepsis is a systemic inflammatory response, and the core mechanism of initiation and progression of sepsis is inflammation ( 13 ). Consequently, a better understanding of the role of the ER in the progression of sepsis is essential so as to identify novel diagnostic markers and therapeutic targets for sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…While berberine was initially approved as an antibacterial agent, it has demonstrated therapeutic potential in some diseases including cardiovascular and neurodegenerative diseases. 54 Berberine has the capacity to interact with a variety of molecular targets, attaching to active spaces characterized by specific structural and physicochemical properties. The effectiveness of berberine about treating the sepsis have been extensively explored in cellular and animal models, although there are no clinical studies on berberine for treating sepsis in practice.…”
Section: Phytochemicals On Sepsis Modelsmentioning
confidence: 99%
“…Additionally, berberine suppresses the phosphorylation of MAPKs, along with reducing the level of reactive oxygen species in macrophages. 54 , 56 Berberine pretreatment has been shown to maintain the integrity of the endothelial glycocalyx, inhibit NF- κ B signaling pathway activation, and decrease the releasing of proinflammatory cytokines such as TNF-α, and IL-6 in LPS-induced ARDS mice model. 57 Studies have also reported that berberine inhibits proinflammatory cytokine expression in bone marrow-derived macrophages and improves survival in septic mice by suppressing NF- κ B- and IL-6-mediated STAT3 activation.…”
Section: Phytochemicals On Sepsis Modelsmentioning
confidence: 99%